The Influence of Education with Audio Visual Media on the Knowledge and Attitude of Postpartum Mothers - Sembiring, Ribka Nova Sartika; Sianipar, Kandace; Nisa’, Khoirun (IJORER : International Journal of Recent Educational Research, 2025)
Objective: Stunting is a condition of failure to thrive in children under five years of age because of chronic malnutrition. This results in children needing to be longer for their age. Malnutrition in children who experience stunting occurs from when the baby is in the womb until after birth co, commonly called the First 1,000 Days of Life (HPK). Children who experience stunting until the age of five will find it difficult to correct so that it continues into adulthood and can increase the risk of offspring with LBW. This study aimed to analyze the effect of Audiovisual Media on stunting on the knowledge and attitudes of postpartum mothers. Method This study used a Quasi-experimental design with a pretest-posttest control group design approach. The sample taken in this study were all postpartum mothers on days 1-14 and met the inclusion requirements in Setia Negara Village, Siantar Sitalasari District, amounting to 30 respondents. Results: The study showed that respondents' knowledge increased by 7.27 and attitudes by 23.7. The statistical test results showed a significant effect of audiovisual media on knowledge and attitudes (p <0.001). Audiovisual media can increase mothers' knowledge by attracting respondents' attention and increasing understanding in mothers with toddlers. Providing health education to the community can increase knowledge and skills in health behavior. Novelty: Providing education using modern technology through audiovisuals can provide new scientific contributions to maternal health education.